2011
DOI: 10.1111/j.1742-6723.2011.01447.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide/oxygen compared with fentanyl in reducing pain among adults with isolated extremity trauma: A randomized trial

Abstract: Neither nitrous oxide/oxygen or fentanyl appeared to be superior to the other in relieving moderate to severe pain among emergency patients presenting with isolated limb fracture or dislocation. In an ED, increased use of nitrous oxide might reduce the overall need for opiate analgesia, and in our setting, the need for constant monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 18 publications
0
34
0
1
Order By: Relevance
“…In a clinical trial, Kariman et al evaluated the effect of 50% Nitrous Oxide/Oxygen compared with fentanyl in reducing the pain caused by bone fractures. The results of this study have shown that the effect of nitrous oxide is similar with Fentanyl and also the complications of these 2 medicines show a significant difference (15). Furthermore, in another clinical trial, Ducasse et al evaluated the effect of nitrous oxide %50 in pain management of patients with trauma.…”
Section: Discussionmentioning
confidence: 93%
“…In a clinical trial, Kariman et al evaluated the effect of 50% Nitrous Oxide/Oxygen compared with fentanyl in reducing the pain caused by bone fractures. The results of this study have shown that the effect of nitrous oxide is similar with Fentanyl and also the complications of these 2 medicines show a significant difference (15). Furthermore, in another clinical trial, Ducasse et al evaluated the effect of nitrous oxide %50 in pain management of patients with trauma.…”
Section: Discussionmentioning
confidence: 93%
“…Selection of ideal and relatively pain-free reduction method could play a key role in management of shoulder dislocations. Intravenous sedation-analgesia (IVSA) is commonly applied for reduction in EDs and provide a trouble-free condition 1, 4, 6, 7, 8, 9, 10, 11. Studies showed that IVSA can trigger some side effects such as central nervous system and cardio-respiratory depression, which requires close patient monitoring and medical management 4, 6.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in an emergency setting, a study compared N 2 O and fentanyl, but the study had multiple limitations (unblinded design, analgesia delayed until after x-ray diagnosis, and nonconsecutive patients). 7 The goal of this investigation was to evaluate the efficacy of N 2 O and oxygen compared to medical air (MA) for prehospital treatment of adult patients with moderate traumatic acute pain. The primary outcome variable was the percentage of patients experiencing analgesia (defined by a numeric rating scale [NRS] score of 3 of 10 or lower) at 15 minutes.…”
mentioning
confidence: 99%